LAW OF MARRYING DAUGHTER OUT OF WEDLOCK BY BIOLOGICAL FATHER IN SHAFI'I AND HAMBALI MADHHABS - Fadil, Fadil; Syaifudin, Muh; Aziz, Qiqiya Tantowi (Pascasarjana Universitas Wahid hasyim Semarang, 2024)
AbstractThis study aims to explore the views of the two main madhhabs in Islam, namely Shafi'i and Hambali Madzhabs, regarding the law of marrying daughters out of wedlock by their biological fathers. This research is done to understand the Islamic legal perspective of such marriages, a complex and challenging issue in Muslim societies.This study used normative and comparative legal methods. The normative method of law is focused on the analysis of Islamic law from the perspective of Shafi'i and Hambali Madhhabs related to the marriage of an extramarital daughter by her biological father. Meanwhile, the comparative method compares the views of the two madhhabs related to the same case. Data sources include primary legal materials, such as the Quran and hadith, and books, as well as secondary legal materials, such as data from the book of 4 madzhab and other books. The data collection techniques used were literature studies and interviews with Islamic jurists from both madhabs.From the research conducted, it was found that, according to Madzhab Shafi'i, the law of marrying a daughter out of wedlock by her biological father is invalid. Imam Shafi'i argued that a child born out of wedlock has no sexual relationship with his biological father, so a marriage between an adulterous daughter and her biological father is considered valid in his view. Meanwhile, according to Imam Hambali, if a woman becomes pregnant out of wedlock and is married by a man who impregnates or does not impregnate her, then the marriage is invalid or void because a pregnant woman, due to adultery, has an iddah period that is until her child gives birth. The child born cannot be sacrificed to his biological father but is still sacrificed to his mother and her family.Keywords: Biological Fathers, Extramarital Children, Marital Guardians